2021
DOI: 10.1111/syen.12473
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new classification of Muscidae (Diptera): a comparison of hypotheses based on multiple molecular phylogenetic approaches

Abstract: Muscidae are a megadiverse dipteran family that exhibits extraordinary diversity in morphology and life history as both immatures and adults. The classification of Muscidae has been long debated, and most higher‐level relationships remain unknown. In this study, we used multilocus Sanger sequencing (mS‐seq), anchored hybrid enrichment (AHE) and restriction‐site associated DNA sequencing (RAD‐seq) approaches to examine relationships within Muscidae. The results from AHE and RAD‐seq largely correspond to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 102 publications
3
28
0
Order By: Relevance
“…Nextgen phylogenomic methods, especially Anchored Hybrid Enrichment (AHE) [70] and Ultraconserved Elements (UCE) [71], comparative transcriptomics [8,20] and draft genome sequencing [72] have rapidly expanded the availability of phylogenetic data useful for resolving relationships within rapid radiations, and for investigating enigmatic relationships, such as those described above for Ephydroidea. In Diptera, the use of Anchored Hybrid Enrichment has yielded important data sets for large families [73][74][75]. A Diptera specific probe kit (NCSU-Wiegmann), has been shown to capture hundreds of single-copy orthologous loci and provide unprecedented resolution for phylogenetic questions at multiple levels-from superfamilies to species.…”
Section: Plos Onementioning
confidence: 99%
“…Nextgen phylogenomic methods, especially Anchored Hybrid Enrichment (AHE) [70] and Ultraconserved Elements (UCE) [71], comparative transcriptomics [8,20] and draft genome sequencing [72] have rapidly expanded the availability of phylogenetic data useful for resolving relationships within rapid radiations, and for investigating enigmatic relationships, such as those described above for Ephydroidea. In Diptera, the use of Anchored Hybrid Enrichment has yielded important data sets for large families [73][74][75]. A Diptera specific probe kit (NCSU-Wiegmann), has been shown to capture hundreds of single-copy orthologous loci and provide unprecedented resolution for phylogenetic questions at multiple levels-from superfamilies to species.…”
Section: Plos Onementioning
confidence: 99%
“…Larval morphology of Muscidae, particularly details of the cephaloskeleton, provides valuable phylogenetic information and is also a rich source of information on larval feeding habits (Grzywacz et al, 2021; Skidmore, 1985). Our results confirm the position of the genus Passeromyia within Reinwardtiinae on the basis of features shared with other members of the subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature concerning the larval morphology of Passeromyia encompasses two early contributions that were limited in material and scope (Skidmore, 1985; Zumpt, 1965). The well‐established relationship between larval cephaloskeletal structure and evolutionary adaptation to feeding strategy (Ferrar, 1979; Roberts, 1970; Skidmore, 1985) has been utilized in taxonomic and systematic research (Grzywacz et al, 2021; Szpila, 2010). Morphological analysis of the larval stages has traditionally involved examination by light microscopy, and more recently, light microscopy combined with scanning electron microscopy (SEM) (e.g., Grzywacz, 2013; Grzywacz & Pape, 2014; Velásquez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This tribe is now suspected of being paraphyletic, because molecular studies (Kutty et al 2014(Kutty et al , 2019 nest Stomoxyini within the Muscini as presently understood. Grzywacz et al (2021), based on molecular approaches, even suggested a classification in which the traditional Muscini genera Mesembrina and Polietes are moved to the Azeliinae. This classification is not adopted here in the absence of morphological support.…”
Section: Subfamily Muscinae Latreille 1802mentioning
confidence: 99%